"Coming out" … as a translator? Expertise, identities and knowledge practices in an LGBTIQ* migrant community translation project. Issue 2 (4th May 2019) - En, Michael; En, Boka
ABSTRACT: In recent years, there has been increasing interest in translation studies in translation projects involving unpaid, "non-expert" translators. At the same time, the fields of science & technology studies and social movement studies have examined the social knowledge practices at work in social movements. This article discusses the case of a translation project by MiGaY, a Vienna-based activist organization dedicated to LGBTIQ* migrants in Austria. In 2016, MiGaY published a text on "coming out" that pays specific attention to the challenges faced by LGBTIQ* migrants. Drawing on Thomas Gieryn's notion of boundary-work, this article examines how translation expertise is negotiated in relation to "translation", "activism", and "LGBTIQ*" questions. It proposes a distinction between identity position (e.g. an "expert" or "lay" translator) and knowledge practices (i.e. actual, contextually contingent knowledge processes), since these do not necessarily coincide.